2015
DOI: 10.1097/cad.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the NOTCH pathway using γ-secretase inhibitor RO4929097 has limited antitumor activity in established glial tumors

Abstract: Notch signaling is altered in many cancers. Our previous findings in primary pediatric ependymoma support a role for NOTCH in glial oncogenesis. The present study evaluates the γ-secretase inhibitor RO4929097 in glial tumor models. The expression of Notch pathway genes was evaluated using real-time RT-PCR in 21 ependymoma and glioma models. NOTCH1 mutations were analyzed by DNA sequencing. RO4929097 activity was evaluated in vitro and in vivo, as a single agent and in combination, in glioma and ependymoma mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…In a previous study, the GSI treatment in patent ductus arteriosus has been indicated to inhibit the downstream targets of Notch pathway, including HES1, HES2, and HES5 . Additionally, GSI treatment also down‐regulates the NOTCH1 effector genes HES1 and HEY1 in established glial tumors . We also reached a favorable result that GSI, inhibited the proliferation and promoted the apoptosis of breast cancer cells.…”
Section: Discussionsupporting
confidence: 54%
“…In a previous study, the GSI treatment in patent ductus arteriosus has been indicated to inhibit the downstream targets of Notch pathway, including HES1, HES2, and HES5 . Additionally, GSI treatment also down‐regulates the NOTCH1 effector genes HES1 and HEY1 in established glial tumors . We also reached a favorable result that GSI, inhibited the proliferation and promoted the apoptosis of breast cancer cells.…”
Section: Discussionsupporting
confidence: 54%
“…One explanation could be the contribution of NOTCH inhibition in the tumor microenvironment possibly by disrupting tumor angiogenesis [23] or blocking endothelial to tumor cell signaling [2425], which was not addressed in this study. Our findings are in agreement with previous results showing the enhanced therapeutic effect of combined GSI with TMZ ( in vitro and ex vivo ) or GSI with RT ( in vitro and in vivo ) compared to each treatment alone [16, 24, 26]. While these findings are important to move NOTCH inhibitors forward as GBM therapeutics, contribution of GSI to current standard of care treatment (TMZ + RT) has never been reported to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 93%
“…Using 3D organotypic tumor explants, we demonstrated Notch inhibition via a gamma-secretase inhibitor (GSI) is associated with a decrease in GSCs, as well as a decrease in endothelial cells (11). We also demonstrated that combination treatment of tumor explants with Notch inhibition and radiation was more effective than either treatment alone, suggesting a synergistic effect (11, 15). These findings formed the scientific rationale for the design of the present trial.…”
Section: Introductionmentioning
confidence: 70%